Stereopsis and clinical features of esotropia patients accompanied by congenital mild ptosis - Heeyoung Choi; Su-Jin Kim; Seung Ahn Yang; Kwang Eon Han (Kosin Medical Journal)
Background To evaluate binocular function and clinical features in patients with esotropia (ET) accompanied by congenital ptosis. Methods Clinical records of 44 ET patients with congenital ptosis (ET-ptosis group) and 71 age-matched ET patients without ptosis (ET only group) who presented for eye examination between January 2016 and December 2021 were retrospectively reviewed. Best-corrected visual acuity (BCVA), magnitude of esodeviation and stereopsis at the first visit were reviewed. Stereopsis and other clinical features of the two groups were compared. Results The mean (±standard deviation) age of overall patients was 5.7 (±1.9) years. The margin reflex distance 1 (MRD1) of patients with ptosis was greater than 0 but less than or equal to 2, indicating that mild ptosis was included. There was no significant difference in the distribution of age, sex, spherical equivalent refractive errors, BCVA, or magnitude of ET (at distance or near) between the two groups (all p>0.05). Furthermore, stereopsis and the number of patients with amblyopia did not differ significantly between the two groups. The magnitudes of esodeviation, near stereopsis and BCVA did not differ significantly between the 0<MRD1≤1 group and the 1<MRD1≤2 group. Conclusions In patients with ET and congenital mild ptosis, stereopsis and visual acuity were not different from those in ET only patients. The presence of coexisting mild ptosis might not have a further deleterious impact on binocular function in ET patients.